STRATEGI FUNDRAISING ZAKAT PADA LAZ NURUL FIKRI KALIMANTAN TENGAH - Zulkifli; Arif Mubarok; Faris Rafi Asshiddik Ravieq (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2022)
The peak of the increase in the collection of social funds by LAZ Nurul Fikri, Central Kalimantan, was when the forest fire disaster and caused smog that hit various areas in Central Kalimantan in 2016. LAZ Nurul Fikri is widely known both in Central Kalimantan itself and from outside the Central Kalimantan region. Since the outbreak of the pandemic, LAZ Nurul Fikri has experienced a decline in associations, but LAZ Nurul Fikri can still survive until now by making various changes to the zakat management strategy, especially the fundraising strategy. This study aims to determine the fundraising strategy of zakat funds implemented by LAZ Nurul Fikri Central Kalimantan. The research method used is qualitative-descriptive research, then the data is processed by triangulation method. The results of this study indicate that the LAZ Nurul Fikri strategy in Central Kalimantan is oriented to muzakki segmentation, and the collection system has undergone a change from direct fundraising, starting to shift to indirect fundraising since the pandemic. There are nine main fundraising strategies for LAZ Nurul Fikri, namely customer segment, value propositions, channels, revenue streams, customer relationships, key resources, key activities, key partnerships, cost structure.